Weak, Seismogenic Faults Inherited From Mesozoic Rifts Control Mountain Building in the Andean Foreland. (15th March 2022) - Wimpenny, Sam
Abstract: New earthquake focal mechanism and centroid depth estimates show that the deformation style in the forelands of the Andes is spatially correlated with rift systems that stretched the South American lithosphere in the Mesozoic. Where the rifts trend sub‐parallel to the Andean range front, normal faults inherited from the rifts are being reactivated as reverse faults, causing the 30–45 km thick seismogenic layer to break up. Where the rift systems are absent from beneath the range front, the seismogenic layer is bending and being thrust beneath the Andes like a rigid plate. Force‐balance calculations show that the faults inerhited from former rift zones have an effective coefficient of static friction μ ′ < 0.2. In order for these frictionally weak faults to remain seismogenic in the lower crust, their wall rocks are likely to be formed of dry granulite. Xenolith data support this view, and suggest that parts of the lower crust are now mostly metastable, having experienced temperatures at least 75–250° C hotter than present. The conditions in the lower crust make it unlikely that highly pressurized free water, or networks of intrinsically weak phyllosilicate minerals, are the cause of their low effective friction, as, at such high temperatures, both mechanisms would cause the faults to deform through viscous creep and not frictional slip. Therefore pre‐existing faults in the Andean forelands have remained weak and seismogenic after reactivation, and have influenced the style of mountain building in South America. However, the controls on their mechanical properties in the lower crust remain unclear. Plain Language Summary: This study is concerned with the controls on how mountain ranges grow. I show that the locations and types of earthquakes along the margins of the Andes mountains, which are generated when the mountain range grows, vary systematically with the positions of ancient fault zones. Where ancient faults lie along the margins of the Andes the entire crust is breaking up through slip on these faults. Where the same faults are not present along the margins of the Andes, the crust is being pushed beneath the mountains like a rigid plate. Therefore, the strength of faults along the margins of the Andes play a critical role in the growth of the mountain range. Notably, the earthquake‐generating faults along the margins of the Andes are much weaker than predicted by laboratory experiments, and the physical reason for their weakness remains unclear. Key Points: New earthquake data show the Andean forelands are breaking up in compression to 30–45 km depth in areas that experienced Mesozoic rifting Force‐balance calculations demonstrate that the effective coefficients of static friction on faults inherited from the rifts is <0.2 These frictionally weak, seismogenic faults control the style of active mountain building in the forelands